The great beauty - Sorrentino, Paolo; Contarello, Umberto; Servillo, Toni; Verdone, Carlo, 1951-; Ferilli, Sabrina, 1964-; Buccirosso, Carlo; Forte, Iaia, 1963- (Criterion collection (Blu-ray discs), 2014)
For decades, journalist Jep Gambardella has charmed and seduced his way through the glittering nightlife of Rome. Since the legendary success of his only novel, he has been a permanent fixture in the city's literary and elite social circles. But on his sixty-fifth birthday, Jep finds himself taking stock of his life, turning his cutting wit on himself and his contemporaries, and looking past the lavish nightclubs, parties, and cafes to find Rome itself, in all it's monumental glory.